Pengaruh Gaya Komunikasi Pimpinan Terhadap Loyalitas Karyawan SD Bonavita - Faula Masniari (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The purpose of this study is to find out whether there is an influence of leadership communication style on the loyalty of SD Bonavita employees. This study uses a quantitative approach. The population in this study is a number of employees of SD Bonavita, which is 39 respondents. The theory used in this study is the Activation Theory of Information Exposure. The results of the study found that the Leadership Communication Style had a partial effect on the loyalty of SD Bonavita employees. The results of the Coefficient of Determination Test found that Communication Style affected Employee Loyalty by 0.902 or 90.2%, indicating that the Influence of Communication Style on Employee Loyalty of SD Bonavita was 90.2%, while 9.8% was influenced by other factors, which means that the influence was very strong.